Challenges to Mental Health Security and Safety of Older Adults in the U.S. - Csikai, Ellen L. (Magyar Gerontológia, 2020)
Although rates of Covid-19 infection are lower for older adults, the mortality rates are higher than all other ages. While the health challenges are evident, the mental health effects of the pandemic are less evident. The term “compassionate ageism” has been used to describe protection of all older adults as vulnerable groups, however it overlooks individual factors that may mitigate risk and enhance mental health aspects of coping with the realities of the pandemic. Isolation and separation from families and once enjoyed activities, whether residing in their own homes or long-term care facilities, has taken an immeasurable physical and mental health toll on older adults. Safety and security for mental health as well as physical health must be considered in any strategy to try mitigate the effects on the quality of life of older adults during this critical time in our history.